IMPACT OF THEILERIOSIS ON MILK IN NATURALLY INFECTED COWS AND BUFFALOES AT HYDERABAD - Memon, M.I.; Memon; Kachiwal; Soomro; Memon, Meh- ja- been; Sethar, Abdullah (International Journal of Research -GRANTHAALAYAH, 2017)
Study was conducted to investigate the consequences of Theileriosis in naturally infected cattle and buffaloes of urban and peri urban areas of Hyderabad. Chemical analysis of milk of infected cows and buffaloes revealed that protein, ash and lactose were significantly declined (P<0.05) whereas, fat and total solids were significantly increased (P<0.05) in Theileria infected cows and buffaloes, but pH and acidity was unaffected. Financial losses occur in terms of reduced quality and severely decreased quantity of milk and meat. The total financial loss including the mortality and decreased quantity of milk and meat was recorded of Rs. 0.17 million / animal in the current study. Theileriosis is one of the main causes of financial losses for livestock holders.